Driving pressure-guided dynamic PEEP titration reduces atelectasis and improves oxygenation in pediatric laparoscopy: a randomized trial on personalized ventilation strategies - Ling-hui Guo; Jian-gang Li; Ming Zhang; Ji-lin Wu; Chao Xie; Yue Lu; Na Li; Bo Feng; Li-ming Cheng (BMC Anesthesiology)
Abstract Background Pediatric laparoscopic surgery often induces atelectasis due to pneumoperitoneum, postural changes, and immature respiratory physiology, increasing postoperative pulmonary complications (PPCs). Fixed PEEP may fail to address perioperative variability. This study evaluated whether dynamic PEEP adjustment reduces atelectasis and improves oxygenation. Methods Children at moderate or high risk of PPCs undergoing elective laparoscopic surgery were randomized into two groups. Group A had driving pressure-guided individualized PEEP titration at three specified time points: after intubation, before pneumoperitoneum initiation, and after pneumoperitoneum completion. Group B had individualized PEEP titration only after intubation, with this PEEP maintained until the end of ventilation. Both groups received alveolar recruitment maneuvers (ARMs). Observations were conducted at 5 min after tracheal intubation (T1), 20 min post-pneumoperitoneum (T2), 60 min post-pneumoperitoneum (T3), at the end of surgery (T4), and at extubation (T5). The primary outcome were intraoperative lung ultrasound score. Secondary outcomes included incidence of atelectasis, oxygenation index, peak airway pressure, plateau pressure, PEEP, driving pressure, dynamic lung compliance, mean arterial pressure, and heart rate. Results At T4 and T5, Group A showed significantly lower subpleural consolidation scores, total lung ultrasound scores, and atelectasis rates versus Group B (P < 0.05). Oxygenation indices in Group A were higher at T3–T5 (P < 0.05). Post-pneumoperitoneum, Group A’s median PEEP increased to 8 cmH2O (vs. Group B), with lower driving pressure and higher dynamic compliance (P < 0.05). Hemodynamic parameters showed no intergroup differences (P > 0.05). Conclusion Driving pressure-guided dynamic PEEP titration reduces postoperative lung ultrasound abnormalities and atelectasis while improving oxygenation and respiratory mechanics in pediatric laparoscopy, without compromising hemodynamic stability. This strategy supports personalized PEEP optimization. Trial registration This trial was registered on Clinical Trials.gov (Registration No. ChiCTR2300070193, Registration date: 2023-04-04). The trial was retrospectively registered as enrollment began prior to registration.